Seventhday Adventist Center Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Andi Gres Cathrin Iroka; Yohannes Firzal; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru has around 700 registered and baptized congregations. The large number of congregations with joint activities carried out routinely, there is no available place that can accommodate according to capacity. Besides, many young people who have potential in character development need a facility that can accommodate all activities inside or outside the church. Hence, the architect designes a building that can facilitate these activities. The Seventh-Day Adventist Center is a place for worship activities, character development and other activities located in Pekanbaru. The Seventh-Day Adventist Center applies the principles contained in the theme of Contemporary Architecture as a design reference according to the function of the building. The concept of the Seventh-day Adventist Center area is "Seven Enlightenment" which aims to fulfill worship activities that are in accordance with the needs of the Adventist Church. The research methods used include field data collection, literature studies and empirical studies. Contemporary architecture makes the appearance of the building more expressive and contrasting than the surrounding environment. The combination of natural materials and high-tech materials is applied to the facade of the building so as to produce buildings that have strong impressions and appreciation. Key word: Seventhday Adventist Center, Gereja Advent, Arsitektur Kontemporer